THE EFFICIENCY ANALYSIS OF 7 NATIONAL ZAKAT MANAGEMENT ORGANIZATIONS (OPZ) USING DATA ENVELOPMENT ANALYSIS (DEA) - Irma Faikhotul Hikmah; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The purpose of this study was to analyze the efficiency level of the national Zakat Management Organization (OPZ) in Indonesia between 2016 and 2018. The sampling technique used was purposive sampling: the researcher took seven national level OPZ consisting of BAZNAS, Dompet Dhuafa, Rumah Zakat Indonesia, IZI, LAZISNU, Panti Yatim Indonesia Al Fajr and Dewan Da'wah Islamiyah Indonesia with the same variables and WTP (Fair without Exceptions) financial statements status from 2016 to 2018. This research is a Data Envelopement Analysis (DEA) non-parametric quantitative study using Banxia Frontier Analyst version 3.2.2 software. The data used was secondary data obtained from LAZNAS and BAZNAS official websites in Indonesia. The measurement of OPZ efficiency in this study was based on output orientation, while the research model used was the BCC model and the assumption used was VRS (Variable Return to Scale). The approach used was production and intermediation approach. The results of the study showed that in general, the level of efficiency in the intermediation approach was higher than the level of efficiency using the production approach. One DMU was found to be inefficient using intermediation approach while in the production approach, ten DMU were found inefficient. Keywords: Organisasi Pengelola Zakat (OPZ), Data Envelopment Analysis (DEA), efficiency, intermediation approach, production approachREFFERENCE Akbar, N. (2009). Analisis efisiensi organisasi pengelola zakat nasional dengan pendekatan Data Envelopment Analysis (DEA). Islamic Finance & Business Review, 4(2), 760–784.Al-Ayubi, S., Ascarya, & Possumah, B. T. (2018). Examining the efficiency of zakat management: Indonesian zakat institutions experiences. International Journal of Zakat, 3(1), 37–55.Ali, M. & Ascarya. (2010). Analisis efisiensi Baitul Maal Wat Tamwil dengan pendekatan two stage Data Envelopment Analysis (Studi kasus kantor cabang BMT MMU Dan BMT UGT Sidogiri). TAZKIA Islamic Finance & Business Review, 5(52), 110–125.Asfarina, M., Ascarya, & Beik, I. S. (2019). Classical and contemporary fiqh approaches to re-estimating the zakat potential in Indonesia. Journal of Islamic Monetary Economics and Finance, 5(2), 387–418. DOI: https://doi.org/10.21098/jimf.v5i2.1068Banker, R.D., Charnes, A., and Cooper, W.W. (1984). Some models for estimating technical and scale inefficiency in Data Envelopment Analysis.Management Science, 30(9), 1078-1092.BAZNAS. (2018). Statistik zakat nasional 2017. Jakarta: BAZNAS.Badan Pusat Statitistik, 2019, Statistik Indonesia, (Online), http://www.bps.go.id, 20 Desember 2019.Charnes, A., W.W. Cooper, and E. Rhodes. (1978). Measuring the efficiency of decision making units. European Journal of Operation Research, 2(6), 429-44.Departemen Agama. (2003). Keputusan Menteri Agama Republik Indonesia Nomor 373 Tahun 2003, Pelaksanaan Undang-Undang Nomor 38 Tahun 1999 Tentang Pengelolaan Zakat. Jakarta: Depag.Firdaus, M., Beik, I. S., Irawan, T., & Juanda, B. (2012). Economic estimation and determinations of Zakat potential in Indonesia. IRTI Working Paper Series, WP 1433-07(August). Retrieved from http://www.isdb.org/irj/go/km/docs/documents/IDBDevelopments/Internet/Englis h/IRTI/CM/downloads/Working Paper Series/WP-1433-07.pdfKamus Besar Bahasa Indonesia (KBBI) daring (http://kbbi.web.id/pusat, diakses 15 Desember 2019).Mubarok, A., & Fanani, B. (2014). Penghimpunan dana zakat nasional (Potensi, realisasi dan peran penting organisasi pengelola zakat). Permana, 5(2), 7–16.Muharam, H dan R. Purvitasari. (2007). Analisis perbandingan efisiensi bank syariah dengan metode Data Envelopment Analysis (periode tahun 2005). Jurnal Ekonomi dan Bisnis Islam, 2(3), 80-166.Muthia, Nur Najmi. (2017). Efisiensi Organisasi Pengelola Zakat (OPZ) dalam mengelola dana zakat di Indonesia. Skripsi tidak diterbitkan. Jakarta: Universitas Islam Negeri Syarif Hidayatullah.Parisi, S. Al. (2017). Tingkat efisiensi dan produktivitas lembaga zakat di Indonesia. Esensi, 7(1), 63-72. DOI: https://doi.org/10.15408/ess.v7i1.3687Qutb, Sayyid. (2003). Tafsir Fi Zhilalil-Qur’an di Bawah Naungan Al-Qur’an. Jakarta: Gema Insani Press.Republik Indonesia. Undang-undang Nomor 23 Tahun 2011 tentang Pengelolaan Zakat. 2011. Jakarta: kemenag.go.id.Republik Indonesia. Undang-Undang Nomor 38 Tahun 1999 tentang Pengelolaan Zakat. 1999. Jakarta: Kemenag.go.id.Rokhlinasari, S. (Tanpa Tahun). Teori–teori dalam pengungkapan informasi corporate social responbility perbankan. Jurnal Al-Amwal: Jurnal Kajian Ekonomi dan Perbankan Syari’ah, 7(1), 1–11. DOI: 10.24235/amwal.v7i1.217Rustyani, S., & Rosyidi, S. (2018). Measurement of efficiency and productivity of zakat institutions in Indonesia using Data Envelopment Analysis and the Malmquist Productivity Index. International Journal of Zakat, 3(3), 69–82. Retrieved from https://ijazbaznas.com/index.php/journal/article/view/98Rusydiana, A. S. (2018). Perubahan teknologi dan efisiensi pada organisasi. Liquidity, 7(2), 124–136.Siswandi dan Arafat. (2004). Mengukur efisiensi relatif kantor cabang bank dengan menggunakan metode DEA, dalam Majalah Usahawan. No.1 XXXIII.Suhail, Adam, F., & Jajang W Mahri, A. (2019). The efficiency of zakat institutions in Indonesia in 2012-2016. KnE Social Sciences, 3(13), 784. DOI: https://doi.org/10.18502/kss.v3i13.4247Suryani & Hendryadi. (2015). Metode riset kuantitatif teori dan aplikasi pada penelitian bidang manajemen dan ekonomi Islam. Jakarta: Prenada Media Group.Tanjung, Hendri dan Abrista Devi. (2013). Metodologi penelitian ekonomi Islam. Jakarta: Gramata Publishing.Thomas, L., & Deci, L. G. V. (2020). Review reviewed work(s): Decision making with the Analytic Network Process: Economic, political, social and technological applications with benefits , opportunities , costs and risks by Thomas L . Saaty and Luis G. Vargas.Wahab, N. A., & Rahman, A. R. A. (2012). Productivity growth of zakat institutions in Malaysia: An application of data envelopment analysis. Studies in Economics and Finance, 29(3), 197–210. DOI: https://doi.org/10.1108/10867371211246876Wahyuny, I. (2016). Efisiensi organisasi pengelola zakat nasional dengan metode Data Envelopment Analysis. Journal of Islamic Economics Lariba, 2(1), 1–12. DOI: https://doi.org/10.20885/jielariba.vol2.iss1.art1Yumanita, D. & Ascarya. (2006). Analisis efisiensi perbankan syariah di indonesia dengan Data Envelopment Analysis. TAZKIA Islamic Finance and Business Review, 1(2), 1–27.